Delayed release phosphatidylcholine as new therapeutic drug for ulcerative colitis: a review of three clinical trials - Stremmel, Wolfgang; Hanemann, Anja; Gauss, Annika; Stoffels, Sabine; Karner, Max; Fazeli, Sahar; Ehehalt, Robert (Expert opinion on investigational drugs, 2010)
Importance of the field: As the pathogenesis of ulcerative colitis (UC) is unknown, a causative therapy is lacking. Therefore, some UC patients suffer from disease activity despite symptomatic anti-inflammatory treatment strategies. We claim that reduction of phosphatidylcholine (PC) in colonic mucus impairs the mucosal barrier and, thus, causes attacks of the commensal bacterial flora to induce colitis. Thus, mucus PC substitution could provide a causal therapy for UC.Areas covered in this review: A delayed released oral PC preparation (rPC) was found to substitute for the lack of PC in rectal mucus. In non-steroid-treated active UC, 53% of rPC-treated patients reached remission compared with 10% of placebo patients (p < 0.001). In a second trial with chronic-active, steroid-dependent UC patients, steroid withdrawal with a concomitant achievement of remission (CAI ≤ 3) or clinical response (≥ 50% CAI improvement) was reached in 15 rPC-treated patients (50%) but only in 3 (10%) placebo patients (p = 0.002).What the reader will gain: The concept that missing PC in colonic mucus is the main pathogenetic factor for development of UC. PC can be substituted by rPC, which cures the disease in the majority of patients.Take home message: rPC is, to our knowledge, the first causative therapeutic option for patients with UC.
Gesehen am 01.09.2023